Health-Related Quality of Life measured with EQ-5D-5L among tuberculosis patients in Addis Ababa, Ethiopia: Institutional-based cross-sectional study. - Tenaw Baye Tarekegn; Getachew Alemkere; Eskinder Eshetu Ali (PLoS ONE, 2025)
Background Tuberculosis (TB) substantially compromises health-related quality of life (HRQoL), yet limited studies have assessed its impact on Ethiopian patients using the EQ-5D instrument. This study evaluates HRQoL, estimates health state utility values, and identifies associated factors among TB patients in Ethiopia. Methods A cross-sectional study was conducted across 20 public health centers in Addis Ababa, Ethiopia, involving 672 TB patients selected via proportional allocation. HRQoL was measured using the EuroQol five-dimension five-level (EQ-5D-5L) tool. Predictors of utility scores were analyzed using the Kruskal-Wallis test and Tobit censored regression models. Results Anxiety/depression was the most frequently affected dimension (55.4% of participants). The mean EQ-5D-5L utility score was 0.91 (SD ± 0.14), and the mean EQ-VAS score was 80.6 (SD ± 15.6). Older age (55-64 years: β = -0.067, p < 0.001; ≥ 65 years: β = -0.383, p < 0.001) and unemployment (β = -0.119, p < 0.001) were associated with significantly lower HRQoL. Conversely, higher income (β = 0.056, p < 0.001), absence of comorbidities (β = 0.059, p < 0.001), and mid-treatment duration (4-5 months: β = 0.029, p = 0.011) correlated with better HRQoL. Conclusion The findings underscore the influence of socio-demographic and clinical factors on HRQoL among TB patients in Ethiopia, calling for targeted interventions and policy reforms to enhance treatment outcomes and patient support.